International Measurement of Disability Purpose, Method and Application - Altman, Barbara M.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This volume provides an informed review of the accomplishments of the Washington Group on Disability Statistics (WG) in the provision of international data and statistics on disability. It does so within the context of the UN Convention on the Rights of Persons with Disabilities. The volume includes a description of the development and testing of a short set of questions for Censuses, now used in approximately 29 countries and recommended in the U.N.'s Principles and Recommendations for Population and Housing Censuses: The 2020 Round, which includes disability as a core topic to be collected in censuses. It discusses the experiences of several countries on the use of the WG questions and how this has impacted on national agendas in the area of disability. It follows the development and testing of an extended set of questions for use in national surveys other than censuses and examines the challenges of translation and the importance of generating comparable question sets in different languages and within different cultures. It studies the examination of cognitive testing techniques in a variety of countries, and presents the results of the first round of censuses in 2010 in countries using the six question set. The volume includes discussions of the new development of question modules on a broad range of child disability and functioning, and the environmental contexts of participation that are part of the current work of the WG. In addition, it contains a reflection on the use of the WG's functionality approach to identifying disabilities by humanitarian agencies to identify disabilities in populations of displaced persons. A thoughtful conclusion addresses what the development of cross-nationally comparable data can mean for the improvement of circumstances for all persons with disabilities.
Dedication -- Introduction - Barbara M. Altman, Washington Group Secretariat -- I Origin of the Washington Group and Issues in Disability Data Collection -- 1 Background and Origin of the Washington Group: Improving the State of Disability Data - Julie D. Weeks, Washington Group Secretariat -- 2 Cross-national Issues in Disability Data Collection - Marguerite Schneider, South Africa -- 3 Processes and Milestones of Washington Group - Cordell Golden, Washington Group Secretariat -- II Census Questions: Purpose, Process and Testing -- 4 Purpose of an International Comparable Census Disability Measure - Barbara Altman, Washington Group Secretariat and Elizabeth Rasch, United States -- 5 Summary of Washington Group Question Evaluation Studies - Kristen Miller, United States -- 6 The Harmonized Joint Pilot Tests for 2010 Population Census Round in Latin American Countries: An Integration Experience - Alicia Berkovich, Brazil -- III Moving Forward: Extended Question Sets and Methodological Advances -- 7 Development of Disability Measures for Surveys: The Washington Group Extended Set on Functioning - Mitchell Loeb, Washington Group Secretariat -- 8 The Asian Testing Experience - Marguerite Schneider, South Africa and Andres Montes, Thailand -- 9 The Challenges of Conducting National Surveys of Disability among Children - Howard Meltzer, England -- 10 Building a "Module on Child functioning and Disability" - Roberta Crisalesi, Elena DePalma, Alessandra Battisti, and Children's Workgroup, Italy -- 11 Cognitive Analysis on Survey Questions for Identifying Out-of-School Children with Disabilities in India - Daniel Mont, England, Sathi Alur, India, Mitchell Loeb, Washington Secretariat, Kristen Miller, United States -- 12 Developing Tools to Identify Environmental Factors as Context for Disability: A Theoretical Perspective - Barbara M. Altman, Washington Group Secretariat and Howard Meltzer, England -- 13 International Comparisons of Disability Prevalence Estimates: Impact of Accounting or not Accounting for the Institutionalized Population - Emmanuelle Cambois, Carol Jagger, Wilma Nusselder, Herman Van Oyen, Jean-Marie Robine, France -- IV Conclusions: Outcomes and Place of the Washington Group Measures in International Data -- 14 The Washington Group on the Improvement of Disability Statistics Globally: Perspectives from the Philippines - Romy Virola and Jessamyn O. Encarnacion, Philippines -- 15 International census/survey data and the short set of disability questions developed by the Washington Group on Disability Statistics - Mitchell Loeb, Washington Group Secretariat -- 16 Swift and systematic? Identifying and recording disability in forced migration - Mary Crock and Laura Smith-Khan, Australia -- 17 The Washington Group's Contribution to Disability Statistics and a Look to the Future -- Jennifer Madans, Washington Group Secretariat -- 18 What if There Were No Washington Group? - Mary Chamie. and Judy Heumann, United States.
Keywords: Quality of life -- Research; Educational tests and measuremen; Statistics for Social Sciences, Humanities, Law